New Trends in Robotics and Automation (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
Robotics and automation technologies have significantly impacted various sectors like agriculture, healthcare, and transportation, contributing to societal advancements and driving the Fourth Industrial Revolution. To sustain progress, it is crucial to explore emerging trends in these fields. With rapid developments in AI, digital twins (DT), IoT, and human–computer interaction (HCI), robotics and automation offer vast opportunities for innovation.